A smart combination: A study on viscosity influences on SMART RHESINS using COMPASS - Günther, Johanna; Feye, Julia; Kampf, Thomas; Rückert, Martin Andreas; Reichl, Teresa; Tietze, Rainer; Roesky, Peter W.; Rösch, Esther; Behr, Volker Christian; Vogel, Patrick (International Journal of Magnetic Particle Imaging, 2025)
To enable reliable quantification of magnetic nanoparticles, new methods for preventing interaction of particles with their physiological environment are necessary. An innovative approach are SMART RHESINs, where conventional nanoparticles are encapsulated in hollow nanospheres. Here, a detailed study on Perimag® based SMART RHESINs has been performed utilizing critical offset magnetic particle spectroscopy (COMPASS) to show that the influence of the surrounding medium, which was varied in viscosity, on the particle system can be suppressed using SMART RHESINs.
CRIS-Team Scopus Importer:2025-04-01